EFFECTIVENESS OF OCCUPATIONAL THERAPY USING ROBOT MANIPULATOR FOR ELDERLY - ANIP FEBTRIKO; AMBIYAR; JALIUS JAMA; DEDY IRFAN; OSKAH DAKHI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Physical activity is one part of occupational therapy, especially in the activity of the kneejoint, where the knee joint is an important part of the movement of the human body. Themovement of the knee joint gets weaker as people age, this is experienced by the elderly. Elderlyare elderly people who often experience knee joints, in addition to the age factor of the kneejoint, it is also influenced by post-accidents, strokes and so on which results in weak knee jointfunction. To restore and function the knee joint, a tool that controls the function of the knee jointis needed, namely a robot manipulator. This robot is a tool that works automatically the same asthe function of the leg which can move the knee joint without any effort from human power butcan be controlled via an Android-based smartphone. This robot manipulator tool works andfunctions with instructions via Android in the form of button control facilities that are onAndroid and also uses voice commands to control the robot. This manipulator robot consists ofseveral main supporting components, namely the controller, manipulator, power supply unit,sensor and actutor. This Robot Manipulator provides a speed setting mode on the tool, so that theuser can adjust the speed of the tool according to its capacity. Also, the movement of this toolcan provide convenience and reduce the risk of weak knee joints. Testing and implementingrobot manipulators for the elderly certainly needs to be analyzed for their achievements byanalyzing using the Wilcoxon Rank test, where this test applies the pretest, namely the initialsafeguards before the use of robots and posttest, namely the action after using the manipulatorrobot.